Natamycin photostability in acidified green tea beverage is dependent on mycosporine-like amino acids and epigallocatechin gallate interaction - Teixeira, Gustavo Henrique de Almeida [UNESP]; Ma, Sihui; Stewart, Amanda C.; Wang, Hengjian; O'Keefe, Sean Francis (Elsevier, 2019)
It has been reported that mycosporine-like amino acids (MAA) have photoprotective effect in acidified green tea beverages containing natamycin as additive, but these results were far from conclusive. Therefore, the objective of this study was to further evaluate the photoprotective effect of MAA in acidified green tea stored in different lighting conditions. Reduced natamycin photostability was observed in beverages with pH 3.5 in relation to its natural pH (5.4), especially when stored under high light emitting diode (LED). Additionally, in pH 5.4 epigallocatechin gallate (EGCG) content reduced and natamycin degradation was also observed when beverages where expose to LED and fluorescent light. By adding MAA it was observed a sharp reduction of EGCG content, which led to faster natamycin degradation. When EGCG was added it was observed a better natamycin photoprotection, but it was not observed when MAA + EGCG were added together. To improve natamycin photoprotection it is necessary to increase EGCG content due to the reaction between MAA and EGCG in acidified green tea beverages.
Keywords: Fluorescent light; HPLC-DAD; HPLC-MS; LED; MAA; Palmaria palmata L.